Rheumatologie - Integration in die studentische Ausbildung (RISA): zur aktuellen Struktur der internistischen Rheumatologie an deutschen Hochschulen (RISA III) = Rheumatology - integration into student training (RISA) : current structure of clinical rheumatology in German universities (RISA III) - Riemekasten, Gabriela; Bergner, Raoul; Lorenz, Hanns-Martin (Zeitschrift für Rheumatologie, 2016)
The German Society of Rheumatology and the Committee for Student Training investigated what effects the structures in university medicine have on student teaching. In February 2014 a questionnaire was sent to the teaching staff and Deans of each of the 37 medical faculties. Of the locations seven were classified as being independent rheumatological university hospitals and nine universities had a W2/W3/C3 grade professor as head of a department of clinical rheumatology but answerable to superiors. In the 37 faculties in Germany the proportion of lecture hours, the proportion of obligatory lecture hours, the number of hours for practical exercises and the number of hours for bedside teaching were distributed very differently and as a rule higher in universities with academic freedom. Not all medical faculties have obligatory teaching in the field of clinical rheumatology. On average medical students see five patients with rheumatological symptoms during their studies. In summary, over the past years it has not been possible to successfully utilize the great importance of rheumatology for society and the innovation potential of this discipline in order to improve the integration of clinical rheumatology into universities.